2019
DOI: 10.31080/asnh.2019.03.0444
|View full text |Cite
|
Sign up to set email alerts
|

Role of Micronutrients on Type Ii Diabetes Mellitus

Abstract: When glucose entered into the blood stream the stored insulin from the pancreas which binds with the zinc will get realized. It has its anti-inflammatory effects where its play a role in abolishing inflammatory markers such as C-reactive proteins. Zinc also helps to get rid of substances that cause inflammation in cells, helps to preserve cell health and insulin sensitivity [8].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…There is an increasing accumulation of evidence linking micronutrient deficiency to diabetes both as a causative factor and as a consequence of the disease [ 71 ]. A systematic review and meta-analysis of the effects of individual micronutrients on blood pressure in patients with type 2 diabetes suggested that vitamin D and possibly vitamin C have beneficial effects on blood pressure, specifically in patients with type 2 diabetes [ 72 ].…”
Section: Role Of Nutrition In Healthy Ageing In Asiamentioning
confidence: 99%
“…There is an increasing accumulation of evidence linking micronutrient deficiency to diabetes both as a causative factor and as a consequence of the disease [ 71 ]. A systematic review and meta-analysis of the effects of individual micronutrients on blood pressure in patients with type 2 diabetes suggested that vitamin D and possibly vitamin C have beneficial effects on blood pressure, specifically in patients with type 2 diabetes [ 72 ].…”
Section: Role Of Nutrition In Healthy Ageing In Asiamentioning
confidence: 99%
“…Several works explained the relation between the trace elements (Zn, Cr, and Mg) and the antidiabetic activity. ey explained also the deficiency of some trace elements in diabetic patients that play a great role in the development of diabetes mellitus [64][65][66][67]. Ahmed et al reported that several trace elements are significantly reduced in people with diabetes mellitus [67,68].…”
Section: 42mentioning
confidence: 99%
“…Oxidative stress significantly contributes to the pathophysiology of diabetes and its consequences 13 14. Micronutrients regulate the expression of genes, metabolism and the onset or progression of chronic diseases like diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress significantly contributes to the pathophysiology of diabetes and its consequences. 13 14 Micronutrients regulate the expression of genes, metabolism and the onset or progression of chronic diseases like diabetes. Micronutrient deficiencies of zinc, chromium, magnesium, copper, manganese and vitamin B are linked to glucose intolerance.…”
Section: Introductionmentioning
confidence: 99%